Climate change perceptions and responsive strategies in Benin: the case of maize farmers - SOGLO, YAO MARCEL YVES; Nonvide, Gbêtondji Melaine Armel (My University, 2019)
Climate change has become a global concern with important impacts in all regions of the world, especially in agriculture sector. In response, farmers take different adaptation strategies to minimise the negative impacts of climate change. This study provides answers to how farmers perceive climate change and what drives their adaptation decisions. To do this, data were collected from a random sample of 200 maize farmers in the municipality of Zè, Benin. Results indicated that almost all the maize farmers perceived change in climate variables. The adaptation strategies used by maize farmers in the municipality of Zè included adjustment in sowing time, use of improved crop varieties, crop and livestock integration and tree planting. Estimates of the multivariate probit model revealed that farmers’ capacity to choose a specific adaptation strategy is affected by age, gender, marital status, education, experience in maize production, credit, distance to market, ownership of TVand agricultural training. These results suggest the need for institutional and technology support measures in adapting to climate change.
Keywords: Climate change; perceptions; responsive strategies; maize